(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
Manufacturing sector has occupied an important role in India’s Economic Development. India is globalising its product more worldwide by ensuring vocal about local products which in turns leading to more start-ups, self-production, and employment opportunities’. Self-reliant is leading India towards sustainability. Sustainability focuses on meeting the needs of the present without compromising the ability of future generations to meet their needs. In India, focus on Manufacturing sector have been increased to make India self-reliant and generate more employment opportunities. Prime Minister of India, Mr. Narendra Modi, had launched the ‘Make in India’ program to place India on the world map as a manufacturing hub and give global recognition to the Indian economy. The Government of India has taken several initiatives to promote a healthy environment for the growth of Manufacturing Sector in the country. The Manufacturing Sector of India has the potential to reach US 1 trillion by 2025 with impetus on developing industrial corridors and smart cities; the government aims to ensure holistic development of the nation. The corridors would further assist in integrating, monitoring, and developing a conducive environment for the industrial development and will promote advance practices in Manufacturing Sector. India is an attractive hub for foreign investments in the Manufacturing Sector. Several mobile phone, luxury and automobile brands, among others, have set up or are looking to establish their manufacturing bases in the country. In today’s COVID19 pandemic, there is focus of India to be self -reliant and every country is promoting its Manufacturing Sector. In this paper, financial performance and Capital structure of Automobiles sector listed on BSE 500 for last 10 years will be analysed to know the overall growth of this sector for making India self- reliant. Various parameters will be analysed in relation to ratios, trend analysis, descriptive statistics, correlation for predicting the growth of automobile sector in the last ten years. Data will be collected from CMIE Prowess. Government initiatives to boost up the manufacturing sector will also be analysed. This paper will help Government, Policy Makers, Industrialist, and the Economist to find more paved ways of economic development through automobile manufacturing sector.